The power of woman : the life and writings of Sarah Moore Grimke - Durso, Pamela R. (Macon, Ga. : Mercer University Press, 2003)
"Sarah Moore Grimke (1792-1873) wanted to become a "useful member of society," a goal she met through her impressive contributions to American social reform during the 1830s. The issue that loomed largest during that decade was slavery, and Sarah became a spokeswoman for and a leader in the abolition movement. As a Southern gentlewoman, her contributions were unique in that she critiqued the institution based on personal experience." "But Sarah did more than fight for the rights of slaves. Perhaps her greatest contribution was as an advocate of women's rights. Her feminist beliefs are set forth in her Letters on the Equality of the Sexes (1838). In this collection of letters, she implemented a new hermeneutic to interpret biblical verses traditionally considered to subject women to the tyranny of men. She confronted the subjugation of women based on divine authority and rejected patriarchal interpretations of Scripture. Based on her interpretation of Scripture, Sarah advocated full equality for women in education, vocation, politics, and finances. She became a role model for many women who later became leaders in the suffrage movement, and is still a role model for many today. Sarah Moore Grimke confronted racism and prejudice within church, society, and herself." "Most books and articles dealing with the Grimke sisters focus on Angelina, and no biography has been written of Sarah. This is the first book-length treatment of Sarah's life and work, and as such as indispensable reading for those interested in women's studies, racism, suffrage history, and religious history."--BOOK JACKET.
Includes bibliographical references (p. [195]-207) and index.
Keywords: Grimké, Sarah Moore, -- 1792-1873.; Women in Christianity -- Biography; Feminist theology; Women abolitionists -- South Carolina -- Biography; Feminists -- South Carolina -- Biography